Dyadic effects of attitude toward aging on psychological well-being of older Malaysian couples: an actor-partner interdependence model - Momtaz, Yadollah Abolfathi; Tengku Abdul Hamid, Tengku Aizan; Masud, Jariah; Haron, Sharifah Azizah; Ibrahim, Rahimah (Dove Medical Press, 2013)
BACKGROUND: There is a growing body of literature indicating that attitudes toward aging significantly affect older adults' psychological well-being. However, there is a paucity of scientific investigations examining the role of older adults' attitudes toward aging on their spouses' psychological well-being. Therefore, the present study aimed to examine the dyadic effects of attitude toward aging on the psychological well-being of older couples. METHODS: Data for the present study, consisting of 300 couples aged 50 years and older, were drawn from a community-based survey entitled "Poverty among Elderly Women: Case Study of Amanah Ikhtiar" conducted in Peninsular Malaysia. An actor-partner interdependence model using AMOS version 20 (Europress Software, Cheshire, UK) was used to analyze the dyadic data. RESULTS: The mean ages of the husbands and wives in this sample were 60.37 years (±6.55) and 56.33 years (±5.32), respectively. Interdependence analyses revealed significant association between older adults' attitudes toward aging and the attitudes of their spouses (intraclass correlation =0.59; P<0.001), and similar interdependence was found for psychological well-being (intraclass correlation =0.57; P<0.001). The findings from AMOS revealed that the proposed model fits the data (CMIN/degrees of freedom =3.23; goodness-of-fit index =0.90; confirmatory fit index =0.91; root mean square error of approximation =0.08). Results of the actor-partner independence model indicated that older adults' psychological well-being is significantly predicted by their spouses' attitudes toward aging, both among older men (critical ratio =2.92; P<0.01) and women (critical ratio =2.70; P<0.01). Husbands' and wives' own reports of their attitudes toward aging were significantly correlated with their own and their spouses' psychological well-being. CONCLUSION: The findings from this study supported the proposed Spousal Attitude-Well-Being Model, where older adults' attitudes toward aging significantly affected their own and their spouses' psychological well-being. The theoretical and practical implications of the findings are discussed.